Some Bond-Additive indices and Its Polynomial of Cellulose - KANDAN, P.; Subramanian, S. (IndoMS, 2024)
Cellulose is one of the natural bio-polymers which have been extensively used in variousfields due to their valuable and remarkable chemical and physical properties. Due to a key ingredientsof cellulose in various product, it’s applications have widely been recognized in many industries likepharmaceutical, bio-fuel, textiles, etc. The study of graphs using chemistry attracts a lot of researchersglobally because of its enormous application. One such application is studying topological indices is anumerical value of a chemical graph associated to a molecular structure. This work attempts to computecellulose chemical structure using topological indices based on the bond like szeged, Padmakar-Ivan(PI),weighted version of PI and szeged index and its polynomial.